Development of surface roughness models in end milling titanium alloy Ti-6Al-4V using uncoated tungsten carbide inserts - Ginta, Turnad Lenggo; Amin, A. K. M. Nurul; Che Daud, Mohd Radzi; Lajis, Mohd Amri (EuroJournals Publishing, Inc., 2009)
This paper focuses on developing an effective methodology to determine the performance of uncoated WC-Co inserts in predicting minimum surface roughness in end milling of titanium alloys Ti-6Al-4V under dry conditions. Central composite design of response surface methodology is employed to create an efficient analytical model for surface roughness in terms of cutting parameters: cutting speed, axial depth of cut, and feed per tooth. Surface roughness values were measured using a surface roughness measuring instrument- Mitutoyo Surftest model SV-500. Design of expert package was applied to establish the first order and the second order model and develop the contours. The adequacy of the predictive model was verified using analysis of variance.